Батьківські практики українців під час повномасштабної війни - Ананьєва, Евеліна Юріївна (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Магістерська робота присвячена батьківським практикам українців під час повномасштабної війни. Розвиток дітей залежить від батьківських практик, в той же час умови повномасштабної війни можуть негативно на них впливати. Отже, їх вивчення є актуальним. Мета роботи полягає у виявленні батьківських практик українців під час повномасштабної війни. Об’єкт дослідження становлять батьківські практики українців, а предмет - батьківські практики українців під час повномасштабної війни. Батьківські практики у дослідженні визначено як поведінки, що проявляються батьками, що стосуються їхньої взаємодії з дітьми та їхнього виконання своїх батьківських обов’язків. Дослідження складалося з двох етапів. Перший етап передбачав розкриття батьківських практик батьків українських старшокласників, а також регіональних відмінностей у цих практиках. Другий етап вивчення батьківських практик українців під час війни передбачав розкриття цих практик на прикладі харків’ян. Наукова новизна магістерського дослідження полягає у характеристиці батьківських практик українців під час повномасштабної війни, а також розробці та тестуванні якісного інструментарію для дослідження цих практик.

Master’s thesis deals with parenting practices of Ukrainians during the full-scale war. Child development depends on parenting practices, and at the same time the conditions of full-scale war can affect those parenting practices negatively. Therefore, studying them is relevant. The aim of the thesis lies in uncovering parenting practices of Ukrainians during the full-scale war. The research object is parenting practices of Ukrainians, and the research subject is parenting practices of Ukrainians during the full-scale war. The thesis defines parenting practices as behaviors exhibited by parents regarding their interaction with children and their performance of their parental duties. The research comprises two phases. The first phase concerns uncovering parenting practices of parents of Ukrainian high school students, as well as the regional differences in those practices. The second phase of studying the parenting practices of Ukrainians during the full-scale war concerns uncovering these practices using the example of Kharkiv residents. The scientific novelty of the master’s thesis lies in characterizing parenting practices of Ukrainians during the full-scale war, as well as development and testing of qualitative tools for researching those practices.
Науковий керівник: Сорока Юлія Георгіївна, доктор соціологічних наук, доцент, професор кафедри соціології
Keywords: SOCIAL SCIENCES; SOCIAL SCIENCES::Social sciences; батьківські практики; повномасштабна війна; батьківські практики батьків старшокласників; батьківська теплота; батьківський контроль; батьківський контроль; батьківська жорсткість; parenting practices; full-scale war; parenting practices of parents of Ukrainian high school students; parenting practices of Kharkiv residents; parental warmth; parental control; parental harshness